2020
DOI: 10.1159/000509367
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation with Tetrahydrocurcumin Enhances the Therapeutic Effects of Dexamethasone in a Murine Model of Allergic Asthma

Abstract: <b><i>Background:</i></b> Tetrahydrocurcumin (THC) is the major active metabolite of curcumin, which is a dietary factor derived from <i>Curcuma</i> species. Our previous study demonstrated a significant beneficial effect of THC in mice with allergic asthma. Glucocorticosteroids (GCs) are commonly used drugs in asthma. Whether THC supplementation could promote the beneficial effects of GC therapy on asthma has not yet been reported. The current study aimed to investigate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…THC and DEX have comparable therapeutic potential in various pathological contexts. Interestingly, when compared to monotherapy with either THC or DEX alone, the combination of both agents significantly reduced nasal rubbing frequency, mucus hypersecretion, and Th2 and Th17 cell count, and it reduced the related cytokines IL-4, IL-5, and IL-17involved in inflammasome activation and pyroptosis in pulmonary infectious diseases [ 70 , 71 ]. Further research is needed to improve curcumin’s low bioavailability and to investigate the use of dry powder inhalation for asthma to overcome solubility and dissolution issues.…”
Section: Curcumin Inflammasome and Lungmentioning
confidence: 99%
“…THC and DEX have comparable therapeutic potential in various pathological contexts. Interestingly, when compared to monotherapy with either THC or DEX alone, the combination of both agents significantly reduced nasal rubbing frequency, mucus hypersecretion, and Th2 and Th17 cell count, and it reduced the related cytokines IL-4, IL-5, and IL-17involved in inflammasome activation and pyroptosis in pulmonary infectious diseases [ 70 , 71 ]. Further research is needed to improve curcumin’s low bioavailability and to investigate the use of dry powder inhalation for asthma to overcome solubility and dissolution issues.…”
Section: Curcumin Inflammasome and Lungmentioning
confidence: 99%
“…181 In addition, the combination of 0.08% THC and 2.5 mg kg −1 dexamethasone significantly reduced the nasal rubbing frequency, mucus hyperproduction, the number of Th2, Th17 cells and the cytokine levels of IL-4, IL-5 and IL-17A in ovalbumin-induced asthmatic mice. 95 In cancer treatment, THC combined with 5-fluorouracil significantly suppressed the proliferation of TE-1 cells to treat esophageal squamous cell carcinoma, while only 5-fluorouracil did not. 182 These results indicated that THC played a synergistic role in inhibiting squamous cell carcinoma, whose effect was different from 5-fluorouracil.…”
Section: The Combination Of Thc With Other Drugsmentioning
confidence: 97%
“…Recent experimental studies provided strong evidence that certain flavonoids such as quercetin, luteolin, cyanidin, and baicalin exert an anti-allergic effect by upregulating the number of Tregs and restoring the balance between Th17/Treg [164,[168][169][170]. Similarly, curcumin showed a modulatory effect on Th17/Treg imbalance, effectively reducing the differentiation of Th17 cells while significantly increasing the number of Treg subtypes in a murine model of asthma [171][172][173].…”
Section: Effector Phasementioning
confidence: 99%
“…Importantly, evidence suggested that curcumin, by inhibition of the Notch1-GATA3 signaling pathway, is capable of not only attenuating the severity of airway inflammation, but also preventing the development of an allergic inflammatory response when administered before the OVA challenge [272]. Curcumin has also been reported to be efficacious in the reduction in airway remodeling in asthma, with the effect of curcumin on histopathological features being dose-dependent and, at the highest doses, comparable to that of dexamethasone [171,271,273]. Moreover, Wu et al showed that supplementation of curcumin in asthmatic mice could increase the therapeutic efficacy of dexamethasone and even prevent adverse effects caused by glucocorticoid treatment, suggesting potential employment as an add-on therapy in asthma [171].…”
Section: Asthmamentioning
confidence: 99%
See 1 more Smart Citation